Discovery Learning and Mathematical Problem-Solving: Evidence from Elementary Education Classrooms - Syifah, Dinda Nuriyah; Maharbid, Dian Anggraeni (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
Problem-solving ability is one of the essential higher-order thinking skills (HOTS) in mathematics education. However, many elementary students still struggle to apply this skill effectively due to learning models that do not actively involve them in the process. This study aims to determine the effectiveness of the Discovery Learning model on students' mathematical problem-solving abilities. The research used a quantitative approach with a pretest-posttest control group design involving fourth-grade students. The sample consisted of 56 students selected through random sampling, divided into control and experimental classes. Data were collected using validated problem-solving tests and observations of learning implementation. The results showed a significant effect of the Discovery Learning model on students’ problem-solving abilities in spatial geometry. The effect was evidenced by the higher average posttest score of the experimental class (70.2) compared to the control class (51), supported by the t-test result (sig. 0.000 < 0.05). Thus, the Discovery Learning model is proven effective in improving mathematical problem-solving skills and can be recommended as an alternative active and constructive learning strategy.